2016
DOI: 10.1080/01635581.2016.1187280
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Phenolic Compounds Against Doxorubicin-induced Cardiotoxicity: A Comprehensive Review

Abstract: Although doxorubicin (DOX) is among the most widely used anticancer agents, its clinical application is hampered owing to its cardiotoxicity. Adjuvant therapy with an antioxidant has been suggested as a promising strategy to reduce DOX-induced adverse effects. In this context, many phenolic compounds have been reported to protect against DOX-induced cardiotoxicity. The cardioprotective effects of phenolic compounds are exerted via multiple mechanisms including inhibition of reactive oxygen species generation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 160 publications
(180 reference statements)
0
45
0
Order By: Relevance
“…Doxorubicin exhibits toxic effects on cancer cells by intercalating with DNA, by disrupting topoisomerase II-mediated DNA damage repair, and by releasing reactive oxygen species leading to oxidative stress and programmed cell death 42. However, it suffers from serious limitations of cardiotoxicity and drug resistance.…”
Section: Curcumin As a Combinatorial Therapy In Various Cancer Typesmentioning
confidence: 99%
“…Doxorubicin exhibits toxic effects on cancer cells by intercalating with DNA, by disrupting topoisomerase II-mediated DNA damage repair, and by releasing reactive oxygen species leading to oxidative stress and programmed cell death 42. However, it suffers from serious limitations of cardiotoxicity and drug resistance.…”
Section: Curcumin As a Combinatorial Therapy In Various Cancer Typesmentioning
confidence: 99%
“…PARP cleavage was used to detect DNA damage in the cell cultures (PE Mouse Anti-Cleaved PARP, Asp214; BD Biosciences, San Diego, CA, USA). Curcumin (30 µM) and/or paclitaxel (10 nM) were added per 1x10 6 proliferating breast cells. Cells were incubated for 48 h at 37˚C.…”
Section: -Amino Actinomycin D (7-a Ad)/annexin V Assaymentioning
confidence: 99%
“…Currently, treatment with conventional chemotherapeutic drugs for breast cancer is limited, due to issues including poor solubility and multidrug resistance (4). Challenges in breast cancer treatment include the combinations of chemotherapeutic drugs that lead to adverse effects, a high level of heterogeneity from patient to patient, and long-term drug administration, with resistance and recurrence of cancer following treatment (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its antimicrobial effects (Stagos et al, 2012b), resveratrol has been reported to have psychological activity including cognitive capability associated with dementia, and antioxidant activity as well as cardiovascular health (Goutzourelas et al;2015,Fenga et al;2016,Hashemzaei et al;2016, Sinha et al;2016, Razavi-Azarkhiavi et al;.…”
Section: Resveratrol: Well-known Monomeric Stilbenementioning
confidence: 99%